Research on the Harmonious Development of China's Old-age Care Institutions - Li, Jing (Journal of Theory and Practice of Management Science, 2024)
With the development of socialization, old-age care institutions have been paid attention to in the old-age security system. After the occurrence of the "Black Heart Retirement Home" incident, we have to consider the imbalances in the development of old-age care institutions. Analysis of the current imbalance and its causes, hoping to find a solution to the problem of imbalance, to effectively prevent the occurrence of similar incidents, and solve the worry of the elderly.